Using Linked Open Data to Improve Data Reuse in Zooarchaeology - Sarah Whitcher Kansa (Ethnobiology Letters, 2015)
The inability of journals and books to accommodate data and to make it reusable has led to the gradual loss of vast amounts of information. The practice of disseminating selected sub-sets of data (usually in summary tables) permits only very limited types of reuse, and thus hampers scholarship. In recent years, largely in response to increasing government and institutional requirements for full data access, the scholarly community is giving data more attention, and solutions for data management are emerging. However, seeing data management primarily as a matter of compliance means that the research community faces continued data loss, as many datasets enter repositories without adequate description to enable their reuse. Furthermore, because many archaeologists do not yet have experience in data reuse, they lack understanding of what “good” data management means in terms of their own research practices. This paper discusses Linked Open Data (LOD) as an approach to improving data description, intelligibility and discoverability to facilitate reuse. I present examples of how annotating zooarchaeology datasets with LOD can facilitate data integration without forcing standardization. I conclude by recognizing that data sharing is not without its challenges. However, the research community’s careful attention and recognition of datasets as valuable scholarly outputs will go a long way toward ensuring that the products of our work are more widely useful.